Pengaruh Bermain Game Mobile Legends, Pola Komunikasi, dan Manajemen Stress terhadap Kerjasama Tim di Kalangan Remaja Karang Taruna Terban Yogyakarta: Penelitian - Luthfi Umamul Husna; Jumadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of playing Mobile Legends games, communication patterns, and stress management on teamwork among teenagers in Karang Taruna Terban Yogyakarta. This research uses a quantitative approach with a survey method or saturated sampling, where primary data is collected through questionnaires from 50 teenagers in Karang Taruna Terban Yogyakarta. Data analysis was carried out by validity test, reliability test, classical assumption test, multiple linear regression, Z test, F test, and coefficient of determination test using the help of SPSS 26. Overall, this study concluded that playing Mobile Legends Game, communication patterns, and stress management have a positive and significant influence on teamwork among teenagers of Karang Taruna Terban Yogyakarta. This emphasizes the importance of these three factors in shaping the dynamics of effective teamwork in a youth environment.